Publication Trends on Halal Tourism: A Bibliometric Review - Abdullah, Khairul Hafezad (Halalsphere, 2021)
Halal tourism has grown in popularity due to the rise of the Muslim population; howbeit it is still a relatively new field. This study aimed to evaluate halal tourism’s publication trends, research areas, prolific sources, most cited documents, co-authorship concerning authors, institutions and countries, and keywords co-occurrence. Using the Scopus database, 118 halal tourism publications were disseminated between 2010 and 2020. This study found an increase in halal tourism in 2018, and the rate increased to 42 in 2020. It can be construed that halal tourism draws in a variety of research areas. Indonesian scholars have been contributed to 26.42% of the overall publications, which leading 34 other countries. Authors’ keywords of ‘Islamic tourism’, ‘Muslim tourists’, ‘halal hospitality’, ‘customer satisfaction’, ‘halal certification’ and ‘religiosity’ have substantially impacted the online search for information. This bibliometric study offers a comprehensive and in-depth glance at halal tourism, which could aid industry and academia.